The Concept of al-Amwal in the perspective of Contemporary Islamic Law - Rahman, Rahman (Prodi HKI IAI Miftahul Ulum Pamekasan, 2023)
This article would like to explain the concept of al-amwal as part of a discussion of contemporary Islamic legal perspectives. The concept of al-amwal related to possessions is a very important necessity in life that cannot be separated from man. In this context, several forms of amwal include grants, alms, infak, waqf and so on. And the classification of al-amwal is divided into four parts, namely al-amwal al-bathiniyyah, al-amwal al-zhahiriyyah, al-amwal al-khash and al-amwal al-am. This research is a qualitative descriptive method using literature studies obtained from certain literature relevant to this research. The results of this study show that wealth is an important need in human life in seeking wealth for its existence in this world should be directed to the benefit of mankind collectively. Because if you pay attention to the initial process of the creation of nature, which is the wealth given by Allah Almighty, it is not only the property of individuals but also the right of all humans. Al-amwal is a divine gift that must be maintained in life. There is treasure because of entrustment from Him. So to get it there is no prohibition in looking for treasures both conventional and sharia